The Incidence of Congenital Malformation in the Gadjah Mada University Hospital Yogyakarta During 1974-1979 - Irawan Irawan; Achmad Surjono; Sunartini Iman; Ismangoen Ismangoen (Paediatrica Indonesiana, 1983)
A study of the incidence of congenital malformation among 4625 newborns in the neonatal unit, Gadjah Mada University Hospital Yogyakarta, during a period of 5 years (1974 - 1979) is presented. The incidence of 1.64% out of 4625 newborns was found. The three most frequent malformations were hydrocephalus (21%), cleft lip and cleft palate (9.2%) and Down's Syndrome (9.2%). A total of 40% were found in multiparous mothers between 20 +- 34 years of age and of 26% in grandemultiparous mothers older than 35 years. According to Arey's distribution of congenital anomalies, developmental arrest was most prevalent (59.2%).